1986
DOI: 10.1029/jd091id04p05229
|View full text |Cite
|
Sign up to set email alerts
|

Surface ozone distributions and variations from 1973–1984: Measurements at the NOAA Geophysical Monitoring for Climatic Change Baseline Observatories

Abstract: Surface ozone data are presented from up to 12 years of continuous measurements at Point Barrow, Alaska; Mauna Loa, Hawaii; American Samoa, South Pacific; and South Pole, Antarctica. Annual cycle characteristics of the data are described relative to atmospheric mixing and transport processes that give rise to the observed annual ozone distributions. Both positive and negative long‐term trends are exhibited by the data. From examination of trends in the seasonal and monthly data, it is concluded that the cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
119
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(127 citation statements)
references
References 29 publications
(17 reference statements)
4
119
0
1
Order By: Relevance
“…Similarly, ozone depletion events (ODEs) in the polar boundary layer, arising after sunrise, were discovered in the 1980s (1,2,3). These events were found to be related to high concentrations of filterable bromine.…”
mentioning
confidence: 99%
“…Similarly, ozone depletion events (ODEs) in the polar boundary layer, arising after sunrise, were discovered in the 1980s (1,2,3). These events were found to be related to high concentrations of filterable bromine.…”
mentioning
confidence: 99%
“…[2] The importance of halogen chemistry for the tropospheric ozone budget is known since the investigation of sudden ozone depletion in the polar boundary layer (BL) after polar sunrise [Oltmanns and Komhyr, 1986;Bottenheim et al, 1986]. Barrie et al [1988] reported high filterable bromine concentrations during these events, suggesting that Br species are involved in the destruction of ozone.…”
Section: Introductionmentioning
confidence: 99%
“…The Dasibi was periodically calibrated by a traveling secondary standard Dasibi photometer that was itself calibrated to a standard ultraviolet ozone meter maintained by the U.S. National Bureau of Standards [Oltmans and Komhyr, 1986]. An ozone source was used to make weekly calibration checks.…”
mentioning
confidence: 99%
“…Ozone mixing ratio was measured at MLO using a Dasibi ultraviolet photometer from a sampling height of 13 m AGL [Oltmans, 1981;Oltmans and Komhyr, 1986;Oltmans and Levy, 1994]. The Dasibi was periodically calibrated by a traveling secondary standard Dasibi photometer that was itself calibrated to a standard ultraviolet ozone meter maintained by the U.S. National Bureau of Standards [Oltmans and Komhyr, 1986].…”
mentioning
confidence: 99%